Reversible conversion between graphene nanosheets and graphene nanoscrolls at room temperature. Issue 18 (9th March 2018) - Gai, Yanzhe; Wang, Wucong; Xiao, Ding; Tan, Huijun; Lin, Minyan; Zhao, Yaping
Abstract : The reversible conversion between the pristine graphene nanosheets exfoliated from graphite and the pristine graphene nanoscrolls was achieved at room temperature. Abstract : In this paper, the reversible conversion between pristine graphene nanosheets and pristine graphene nanoscrolls at room temperature was reported. The graphene nanosheets were rolled up into the graphene nanoscrolls by silver nitrate in ethanol solution, and the fabricated graphene nanoscrolls were unfolded back to the graphene nanosheets in ethanol solution by adding ammonium hydroxide. The dynamic conversion state of the process was confirmed by the morphology of the intermediate samples captured using an optical microscope and scanning electron microscope. Also, AFM, TEM and Raman spectroscopy displayed that the graphene transformed from its nanoscrolls remained the structure and morphology of the started graphene. The reason for the formation of the nanoscrolls was assigned to the silver cyanide particles generated on the edge of the graphene. The freshly formed silver cyanide caused the unbalanced energy of the graphene surface by changing the pi electron distribution and triggered off the graphene to roll up. The unfolding of the graphene nanoscrolls back to the graphene nanosheets was attributed to the removal of the silver cyanide by the ammonia via forming the complex. This reversible conversion might be a novel and facile approach to make graphene nanoscrolls and to store the graphene. Also, it may bring new sight to the conversion research between two-dimension and one-dimension materials.